Mediastinal epithelioid sarcoma: a case report - Hu, Xianwen; Yu, Ronghua; Li, Song; Cai, Jiong; Pan, Dongfeng (Frontiers in Medicine, 2025)
Epithelioid sarcoma (ES) is a rare soft tissue malignancy of uncertain differentiation that can arise in various anatomical locations; however, its occurrence in the mediastinum is exceptionally uncommon. Herein, we present a 57-year-old woman diagnosed with mediastinal ES. A soft tissue mass in the mediastinum was initially detected incidentally during a routine physical examination; however, the patient did not perceive it as concerning and therefore did not seek further evaluation or treatment. Approximately 5 months later, the patient presented to our hospital with complaints of cough and chest tightness for diagnostic assessment and management. A chest computed tomography (CT) scan revealed a soft tissue density mass in the posterior mediastinum, with visible intratumoral nodular calcifications and mild heterogeneous enhancement on contrast-enhanced CT, findings suggestive of a neurogenic tumor. Subsequently, the patient underwent surgical resection, and postoperative pathological examination confirmed the diagnosis of ES. Unfortunately, during the subsequent imaging follow-up, it was found that the tumor had recurred within a short period of time. ES occurring in the mediastinum is rare, while our case suggests that it should be considered as one of the imaging differential diagnoses for mediastinal or near hilar tumors.